Fostering Critical Intercultural Awareness Among EFL Students Through Critical Discourse Analysis - Hazaea, Abduljalil Nasr (Íkala, Revista de Lenguaje y Cultura, 2020)
This paper reports some findings on the development of critical intercultural awareness among English-as-a-foreign-language students in the context of a critical reading enrichment course for students in the preparatory year at a Saudi university. The critical reading class aimed to increase levels of critical intercultural awareness among the participants when they decoded and encoded an intercultural text. A qualitative action research design was used. The teacher-researcher equipped the participants with tools from critical discourse analysis for analyzing intercultural texts. After that, they were asked to work on an assignment by reading a text about a dinner invitation and then writing creatively on that topic. The study data were collected from these reflective writings in the participants’ portfolios. The teacher-researcher also used tools of critical discourse analysis to analyze the collected data. It was found that the participants demonstrated a balanced intercultural awareness associated with the discourse of food diversity. They also effectively appreciated cultures of the self and others and demonstrated appropriate intercultural knowledge of the self and others. Furthermore, they acquired the intercultural skills of relating to intercultural texts, as well as analyzing and interpreting them. The study suggests the effectiveness of critical discourse analysis as a teaching and learning strategy to increase critical intercultural awareness among English-as-a-foreign-language students.